Assessment of sea wave spectra using a surfaced glider. (August 2015) - Alvarez, A.
Abstract: The determination of non-directional and directional sea wave spectra is attempted by analyzing the dynamical response of a surfaced Slocum glider. The method makes use of the glider heave motion to infer non-directional properties of the wave spectra. In addition, surge and sway motions are considered to derive wave directionality. The transfer functions for heave, surge and sway for a surfaced Slocum glider has been computed to determine the impact of the body geometry/inertia and the angle of incidence on the response of the surfaced platform when excited by regular waves. Numerical results show that for wave periods longer than 6 s, motions measured at the glider platform can be assumed equivalent to motions experimented by the water parcels at the sea surface. Spectral information about sea state conditions can then be directly derived from the measurement of glider responses. Results also reveal a natural period of the surfaced glider at around 5 s. A series of field experiments were conducted during March 7th, May 17th and May 27th of 2013 in a marine region off-shore La Spezia, to validate the methodology. Specifically, the wave spectra derived from a Slocum glider equipped with a set of accelerometers was compared against the values provided by a Datawell Waverider Mk3 moored in the vicinity of the glider deployment. Agreement has been found between the non-directional estimates from the glider and the values measured by the waverider. Regarding wave directionality, glider estimates of peak direction agree well with those reported by the waverider. More significant differences are found between the directional spread estimates. Highlights: The response to waves of a surfaced glider is modeled with a boundary element method. The glider follows the wave surface for wave periods longer than 6 s. The wave spectrum is inferred from glider accelerations for long wave periods. Three experiments were done to assess the wave spectrum with a glider. Non-directional spectrum from the glider agrees with estimates from a Waverider. Direction at peak period from glider agrees with Waverider observations. Directional spread at peak period differs 25% from Waverider observations.